Kinetic Study of Boron Oxide Prepared by Dehydration of Boric Acid - Zhang, Weijiang; Sun, Shuguang; Xu, Jiao; Chen, Zhou (Asian Journal of Chemistry, 2015)
The kinetic parameters of dehydration of boric acid had been investigated by using TG-DTG data and the Doyle method. The reaction took place in two stages and the demarcation point of the two stages was near at a = 0.63. The dehydration was completed with a final solid weight of 56.29 % with two reaction stages in series in the temperature range of 100-800 °C. The activation energy E and frequency factor K for the two stages are143.919 kJ/mol, 3.1874 × 1014 and 69.902 kJ/mol, 2.52367 × 105, respectively. The reaction rate expressions were: